Working the Speaking Skill by Using a Web Page in English Classes - Rodríguez Tamayo, Ilba Yaneth; Barrera Parra, Yelipsa; Burgos Jimenez, Amanda Lizeth; Cuevas Peña, Adriana Lizeth; Lara Vargas, Andrea Nataly (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Information and communication technologies, or ICTs, have gained importance in the globalized world. Meanwhile, they are also a challenge for teachers, who might be reflecting on their teaching practices. The following paper reports on a study developed with sixth graders at a public institution in Tunja, Colombia. The study was implemented during the first semester of 2016, and its goal was to develop speaking skills through workshops organized on a web page. Data was  collected through field notes, students’ artifacts, recordings, and questionnaires. The results showed that the use of ICTs caught the students’ attention, encouraged them to speak English, and increased their vocabulary. Being able to speak and understand more vocabulary could help students use the language in real life situations, as well as reinforce their learning autonomy.